Interpretive Structural Modelling for Determining Dominant Success Criteria of Information System (IS) Success at Handycraft SMEs in Yogyakarta, Indonesia - Sinaga, B.L.; Purnama, I.L.I.; Astanti, R.D.; Putri, N.T.; Wulandari, N.D. (International Journal of Industrial Engineering and Engineering Management, 2019)
The purpose of this research paper is to determine the dominant criteria of Information System (IS) success specific to handcraft SMEs in Yogyakarta and to establish relationship among those criteria using interpretive structural modeling (ISM). A small portion of those SMEs have started using information system. However, they face several barriers to successfully implement the information system. Therefore, it is necessary to ensure the success of information system implementation. But, no study has been done regarding the measurement IS success specific to handcraft SMEs in Yogyakarta. This research involved interview-based surveys and ISM approach to determine the dominant criteria of IS success of SMEs in Yogyakarta context. In total, 16 SMEs were involved as research objects in this research. In this research, four cluster of SME have been identified and the modified IS Success model for each cluster was developed accordingly.  The modified model for each cluster has 14, 20, 16 and 30 criteria respectively. Through ISM, a relationship model among the criteria for each model was also obtained. It was concluded that “ease of use”, “ease of learning”, and “data accuracy” are significant criteria of IS Success model in SMEs in Yogyakarta. These criteria are considered as the dominant criteria to implement information system successfully. In addition, the desired results of successful implementation is represented by “improved outcomes”.